THEORY OF REALISTIC MATHEMATICS EDUCATION: CONCEPTUAL FOUNDATIONS AND CONNECTION WITH PISA MATHEMATICAL LITERACY - Dieorditsa, Taiana; Yepifanova, Olga; Tolmachov, Volodimir (Physical and Mathematical Education, 2025)
Formulation of the problem. The results of PISA 2022 revealed that 42 % of Ukrainian adolescents did not reach the baseline level of mathematical literacy, a figure significantly higher than the OECD average of 31 %. This gap underscores the urgent need to adopt instructional strategies that develop students’ ability to apply mathematical knowledge in real-world contexts. In this regard, the theory of Realistic Mathematics Education (RME), which underpinned educational reforms in the Netherlands, merits particular attention. Despite the growing interest in RME within the international academic and educational communities, this theory remains largely unexplored in Ukraine. This creates the need for an in-depth analysis of its conceptual foundations and an exploration of its connections with PISA mathematical literacy. Materials and methods. This study draws on English-language scholarly publications on the RME theory and the official PISA 2022 framework document. A systematic approach was employed to examine the theoretical underpinnings and methodological principles of RME. In addition, a comparative analysis was conducted to identify potential connections between this theory and the concept of mathematical literacy as outlined in the PISA framework. Results. Based on a systematic study of RME, an analytical model has been developed that comprises three interconnected levels of this theory: conceptual level – encompassing progressive mathematization, didactic phenomenology, guided reinvention, and emergent modeling; methodological level – defined by the principles of reality, activity, levels, interconnection, interactivity, and guidance; applied level – involving practical didactic tools such as horizontal and vertical mathematization. This model is designed to serve as a reference framework for educators, aiming to implement modern approaches to mathematics education. Nonetheless, its abstract nature necessitates further elaboration to ensure effective application in real classroom settings. The comparative analysis also identified structural and methodological parallels between specific components of the RME theory and the conceptual framework of mathematical literacy as defined by PISA. Still, these connections are considered conditional, as RME is a didactic theory, while mathematical literacy is an external assessment tool. Conclusions. The analysis of international experience indicates that RME plays a complex yet promising role in the field of mathematics education. The effectiveness of this theory depends on the specific educational context, the professional training of teachers, and the ability to balance innovative methodologies with established curricular standards. Integrating elements of RME into Ukrainian school education holds the potential to enhance students’ mathematical literacy in line with PISA benchmarks, provided it is thoroughly adapted to the national educational context.